The economic regions of Ecuador , their integration and development. - Banco Central del Ecuador (1961)
In recent years interest in the regional aspects of development planning in under-developed countries has greatly increased. Nevertheless there is as yet not such a thing as a general theory of or a standard approach to regional economic development. A study of the interrelation between national economic planning and regional development programmes can not be based, therefore, upon a body of established methods and previous experiences in this field. Moreover, with respect to the economic regions that may be distinguished in the Ecuadorian economy, a general and systematic analysis has never been made made before. The present study, for both reasons, cannot be more thap a first attempt in this direction.